Respuesta :

Answer:

Equation in point-slope form=  [tex]{y+3}=\frac{-1}{2}(x+3)[/tex]

Step-by-step explanation:

The given end points are B(−1,1) and C(−5,−7)

Mid point M of BC= [tex]\frac{-5-1}{2}[/tex] , [tex]\frac{-7+1}{2}[/tex]

Mid point M of BC = -3 , -3

Slope of BC =  [tex]\frac{-7-1}{-5+1}[/tex] = 2

Slope of bisector= m= [tex]\frac{-1}{2}[/tex]

Equation of perpendicular bisector : [tex]\frac{y+3}{x+3}=\frac{-1}{2}[/tex]

                                                           ⇒   [tex]{y+3}=\frac{-1}{2}(x+3)[/tex]

                                                          ⇒   2(y+3)= -(x+3)

                                                          ⇒  [tex]2y+x=-9[/tex]